Comparison of Changes in Liver Function Tests in Pregnant Women with Mild and Severe COVID-19 - Pooransari, Parichehr; Pouransari, Razieh; Laki, Mahboobeh Gharib; Asl, Zhila Abedi; Yavari, Samira; Hosseiniara, Reza (Coronaviruses, 2025)
ObjectiveSome pregnancies are affected by liver dysfunction, and differentiating them from possible liver dysfunction caused by COVID-19 in pregnancy will lead to a better therapeutic approach and management.AimsThe current study was conducted with the aim of investigating changes in liver function tests (LFTs) in pregnant women with mild and severe COVID-19.MethodsIn this retrospective observational study, 130 pregnant women with COVID-19 were examined in two referral hospitals in Iran in 2021-2022. COVID-19 was confirmed by reverse transcription-polymerase chain reaction (RT-PCR) and WHO guidelines. Pregnant women were assigned into two categories of mild and severe COVID-19 based on clinical symptoms and radiologic chest evaluation. Demographic and clinical data of women were recorded. The level of liver enzymes AST, ALT, ALP, total and direct bilirubin was measured in all patients. Fever, oxygen saturation level, preterm delivery, and maternal mortality were reported as final clinical outcomes and compared in two groups.ResultsForty-nine pregnant women with severe COVID-19 and 81 pregnant women with mild COVID-19 were matched in terms of demographic data. The proportion of women with abnormal AST and ALT in the severe COVID-19 group was significantly higher than in the mild group (p < 0.05). However, the proportion of women with abnormal ALP levels in the mild COVID-19 group was significantly higher than in the severe group. Moreover, there was no significant difference between the two groups in terms of the proportion of women with abnormal levels of total and direct bilirubin. Most pregnant women with severe COVID-19 (50%) had a hepatocellular abnormality, while most women with mild COVID-19 (42%) had abnormalities in cholestasis (p = 0.003).ConclusionAccording to the present findings, liver dysfunction and increased liver enzymes in pregnant women with COVID-19 were related to the severity of the disease, and most women with severe COVID-19 had hepatocellular abnormality, respectively. Therefore, pregnant women with COVID-19 should be closely monitored for LFTs assessment.
Keywords: COVID-19